ON TRANSLATION AND LITERARY VARIATION IN THE COMPILATION OF CLASSICAL CHINESE LITERARY HISTORY. - Peina Zhuang (Comparative Literature Studies, 2020)
The compilation of classical Chinese literary history in English includes another important yet much neglected aspect, that is, the translation of literary works and the consequent literary variation. Based on the analysis of translation and literary variation in the eight English versions of classical Chinese literary history, this paper argues that what to translate and how to translate largely determine the basic configuration of a "history," revealing the interaction between the identity as a translator and that as a history compiler. And also the prevalent literary variation in classical Chinese literary history validates the necessity of rewriting the literary history in a foreign language.